2013
DOI: 10.1002/eat.22223
|View full text |Cite
|
Sign up to set email alerts
|

Differential impairments underlying decision making in anorexia nervosa and bulimia nervosa: A cognitive modeling analysis

Abstract: This study identified differential impairments underlying IGT performance in AN and BN. Findings suggest that impaired decision making in AN might involve impaired memory functions. Impaired decision making in BN might involve altered reward and punishment sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 33 publications
(59 reference statements)
8
91
2
1
Order By: Relevance
“…While previous laboratory investigations (14,15) were relatively limited in 243 their ability to isolate specific alterations, a recent cognitive modelling study of IGT performance 244 found a "recency bias" in AN captured by a learning/memory parameter (58). Although the model 245 did not uncover a group difference in a feedback sensitivity parameter, the finding that patients 246 tended to base their decisions on recent experience is commensurate with our finding of increased 247 learning rate in AN.…”
Section: Imaging Data 187supporting
confidence: 70%
See 1 more Smart Citation
“…While previous laboratory investigations (14,15) were relatively limited in 243 their ability to isolate specific alterations, a recent cognitive modelling study of IGT performance 244 found a "recency bias" in AN captured by a learning/memory parameter (58). Although the model 245 did not uncover a group difference in a feedback sensitivity parameter, the finding that patients 246 tended to base their decisions on recent experience is commensurate with our finding of increased 247 learning rate in AN.…”
Section: Imaging Data 187supporting
confidence: 70%
“…Fourth, the group 302 difference in self-reported HA was not significant in the present study, presumably because of lack of 303 statistical power (SM 2.1), and the expected correlation between HA and learning rate after 304 punishment was not found (SM 2.3). Therefore, alternative explanations of increased learning rate in 305 AN inlcuding impaired memory (58) and uncertainty regarding present beliefs are also plausible. 306…”
Section: Imaging Data 187mentioning
confidence: 99%
“…The use of such models allows one to decompose behavioral performance on the task into distinct cognitive, motivational, and response processes, thereby providing a fine-grained analysis of the underlying decision-making processes and characterizing more precisely the decision-making deficits of different clinical groups. This approach yields quantifiable parameter estimates of such processes, which have been successfully mapped in various clinical populations including cocaine users, cannabis users, alcohol users, individuals with Asperger's disease, Huntington's disease, schizophrenia, and bipolar disorder (for a review, see Yechiam et al, 2005), as well as in eating disorders (Chan et al, 2014) and patients with HIV (Vassileva et al, 2013). Studies applying this approach show that although behavioral performance may be similar across different clinical groups, the cognitive processes that underlie these behavioral profiles may vary across groups in clinically meaningful ways.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this idea, the majority of studies examining decision-making in AN using the IGT have documented worse performance in AN compared to healthy participants (e.g., Abbate-Daga et al, 2011; Cavedini et al, 2004; Cavedini et al, 2006; Danner et al, 2012, Garrido & Subirá, 2013; Tchanturia et al, 2007). This has led to models in which poor decision-making may contribute to the development and maintenance of symptoms in AN (Brogan et al, 2010; Cavedini et al, 2004; Chan et al, 2014). …”
Section: Introductionmentioning
confidence: 99%